Visual literacy in graphic design teaching (Revista de Ensino em Artes, Moda e Design, 2022)
This article aims to discern about the didactic experience in teaching visual syntax content delimited in compositional practice. The research is  qualitative, whose data and information collection  strategies used were bibliographic and systematic  research in a scientific work bank. Next, some  examples of historical landmarks that support the  discussion about the programmatic content of  academic activity are described. At the end, a  discernment about this content in the academic  formation of this future professional is presented,  verifying tensions in the teaching-learning of the  syntactic foundations of visual language in Graphic Design.
Keywords: Visual Literacy; Teaching in Graphic Design; Design Theory